2022
DOI: 10.1186/s12974-022-02582-z
|View full text |Cite
|
Sign up to set email alerts
|

The associations between plasma soluble Trem1 and neurological diseases: a Mendelian randomization study

Abstract: Background Triggering receptor expressed on myeloid cell 1 (Trem1) is an important regulator of cellular inflammatory responses. Neuroinflammation is a common thread across various neurological diseases. Soluble Trem1 (sTrem1) in plasma is associated with the development of central nervous system disorders. However, the extent of any causative effects of plasma sTrem1 on the risk of these disorders is still unclear. Method Genetic variants for plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Shi et al (2022) have investigated the causal role of Trem1 plasma levels on MS, but did not find a statistically significant causal effect on MS risk. The study from Dong et al (2022) has instead investigated the causal role of Trem2 cerebrospinal fluid levels on MS risk.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shi et al (2022) have investigated the causal role of Trem1 plasma levels on MS, but did not find a statistically significant causal effect on MS risk. The study from Dong et al (2022) has instead investigated the causal role of Trem2 cerebrospinal fluid levels on MS risk.…”
Section: Resultsmentioning
confidence: 99%
“…Trem1 belongs to the immunoglobulin Trem family, and it is considered important in inflammatory responses as it contributes to the activation of immune cells and neuronal death in pathological scenarios (Lu, Liu, Sherchan, et al, 2021). Shi et al (2022) have investigated the causal role of Trem1 plasma levels on MS, but did not find a statistically significant causal effect on MS risk. The study from Dong et al (2022) has instead investigated the causal role of Trem2 cerebrospinal fluid levels on MS risk.…”
Section: Trem1 and Trem2 Levelsmentioning
confidence: 97%
“…A P-value < 0.05 indicates that the inverse variance-weighted (IVW) results might be invalid due to horizontal pleiotropy, and an MR Pleiotropy REsidual Sum and Outlier (MR-PRESSO) test should be conducted 30 . The degree of heterogeneity across all SNPs was evaluated using Cochran's Q statistic and leave-one-out analysis 31 . The results of the pleiotropy, heterogeneity, and sensitivity analyses are presented in Supplementary Tables S4 , S5 , and S6 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Mendelian randomization (MR) is a method for inferring causal associations between genetic variants and disease. A recent study applying MR to plasma proteins found that increased plasma levels of the soluble ectodomain of TREM1, or sTREM1, was associated with increased AD risk 41 . We validated this finding independently using plasma proteins measured using a multiplexed, aptamer-based approach (SOMAscan assay) in 35,559 Icelanders 42 to determine which variants associated with plasma sTREM1 and sTREM2.…”
Section: Mainmentioning
confidence: 99%
“…Preclinical studies in mouse models of aging and AD pathology demonstrate that healthy microglial function is lost with advancing age and suggest that disease-modifying components of the innate immune response could be targeted to slow or halt disease progression. A well-studied myeloid receptor associated with AD is TREM2 (Triggering Receptor Expressed on Myeloid cells-2) where loss of function variants increase risk for AD [6][7][8] .TREM2 is an anti-inflammatory innate immune receptor that promotes Aβ clearance 9,10 and microglial survival 11 .In models of amyloid accumulation, microglia lacking Trem2 or harboring the R47H Trem2 variant show deficient proliferation, survival, clustering, phagocytosis, and Aβ plaque compaction [12][13][14][15] .The function of the family member TREM1 (Triggering Receptor Expressed on Myeloid cells-1) is distinct from that of TREM2. In sharp contrast, TREM1 amplifies pro-inflammatory innate immune responses to sterile damage associated molecular patterns (DAMPs) and infectious pathogenic molecular patterns (PAMPs) [16][17][18][19][20] (Fig.…”
mentioning
confidence: 99%